Hazard Investigation for Formwork Installation at High Rise Building Construction - Sheridan, Shazmin; YASAK, FUAD; AB HAMID, AMIN (Progress in Engineering Application and Technology, 2023)
The purpose of this study was to identify these dangers in order to assist construction workers who will use this strategy. The system’s several hazards were identified. When considering solely the activities of the aluminium formwork system, each stage includes several linked dangers, and the worker may be exposed to several hazards in the same activity. Both the hazards and the preventive measures suggested could be used to collect data for future construction projects. They might be used to validate the presence of these and other hazards, as well as to check that builders and other experts are taking the necessary safeguards.